The trouble with Tink - Thorpe, Kiki.; Clarke, Judith; Disney Storybook Artists (New York : Random House Children's Books, 2006)
Tinker Bell, a pots-and-pans fairy who loves fixing things, has lost her hammer and now everything she tries to repair goes wrong, but in order to get her talent back, she may have to visit a former friend who once hurt her feelings.
"A Stepping Stone book."
4.7
3-6
3-6
School Library Journal
690
Keywords: Fairies -- Juvenile fiction; Repairing -- Juvenile fiction; Lost articles -- Juvenile fiction; Friendship -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Fairies -- Fiction; Repairing -- Fiction; Lost and found possessions -- Fiction; Friendship -- Fiction; Characters in literature -- Fiction; Fairies -- Fiction; Repairing -- Fiction; Lost and found possessions -- Fiction; Friendship -- Fiction; Characters and characteristics in literature -- Fiction